The Theory of Strong Position: Navigating Success in a Dynamic World - Abduraxmanova Zilola Yoqubjon qizi; Saidov Sohibxon Sulaymonxonvich (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article delves into the profound concept of the Theory of Strong Position, a guiding philosophy that transcends the boundaries of diverse domains—from professional pursuits to personal relationships. Through a metaphorical lens of navigating turbulent waters, the piece explores how this theory provides individuals and entities with a strategic roadmap for not just weathering life's storms but harnessing their energy for growth. The article concludes with a poignant reflection on adaptability and seizing opportunities—a fitting closure to a narrative that encourages readers to embrace the fluidity of life and secure positions that stand resilient against the test of time